The role of dividend policy as an intervening variable in the influence of financial fundamental factors on blue chip stock returns - Resta Maulita Angreani; Ahmad Shalahuddin; Helma Malini; Giriati Giriati; Wendy Wendy (Trigin Publisher, 2023)
The climate of investment plays a crucial role in the economic structure, where investors seek stocks from companies with a large market capitalization as market leaders because it reflects substantial company growth with relatively low risks. This study is essential as an investor analysis of evaluating the financial condition of a company and assessing the company's ability to survive long-term investment, as well as projections on how to understand the potential of dividend policy in distributing profits. This study will use Software Eviews 12 with multiple regression analysis panel data to test the hypothesis and the intervening variable. The sample data consists of 22 LQ45’s index blue chip companies listed on the IDX 2018-2022 period using a Purposive Sampling approach. Based on the research analysis EPS is not significant for dividend policy, PER has a significant impact on dividend policy, PBV does not impact dividend policy, EPS and PER both have a positive impact on stock returns. PBV, on the other hand, has a negative and significant effect on stock returns. Furthermore, PBV has a negative and significant effect on stock returns. Moreover, dividend policy significantly influences stock returns negatively. Additionally, dividend policy cannot mediate the EPS, PER, and PBV variables on stock returns.